2006
DOI: 10.1007/s10461-006-9193-4
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Risk among Impoverished Women: Understanding the Role of Housing Status

Abstract: HIV/AIDS increasingly affects women, and housing status is important to understanding HIV risk behaviors among women. The goal of this study is to enhance understanding of the association between housing status and a key sexual risk behavior, having multiple sex partners, by investigating the extent to which housing status differences can be accounted for by hypothesized explanatory factors. In a probability sample of 833 women in Los Angeles, results indicated that homeless African American and Hispanic women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 57 publications
7
50
0
Order By: Relevance
“…36 Another study found that women who received federal housing support were half as likely as homeless women of similar economic status to engage in risky sexual behavior. 37 Although most of the data mentioned so far come from the United States, they are substantiated by other studies in Canada, 43 South Africa, 44 and India. 45 These data, along with cost-effectiveness and threshold analyses, suggest that providing stable housing to people living with or most vulnerable to HIV infec- tion is an effective strategy to prevent and mitigate HIV and AIDS.…”
Section: Stable Housingmentioning
confidence: 78%
See 1 more Smart Citation
“…36 Another study found that women who received federal housing support were half as likely as homeless women of similar economic status to engage in risky sexual behavior. 37 Although most of the data mentioned so far come from the United States, they are substantiated by other studies in Canada, 43 South Africa, 44 and India. 45 These data, along with cost-effectiveness and threshold analyses, suggest that providing stable housing to people living with or most vulnerable to HIV infec- tion is an effective strategy to prevent and mitigate HIV and AIDS.…”
Section: Stable Housingmentioning
confidence: 78%
“…[33][34][35] Emerging evidence demonstrates that improvements in housing status also contribute to reductions in HIV-related risk behaviors. [36][37][38][39][40][41][42] One study of more than 2,000 people found that at baseline, recent drug use, needle use, and "transactional" sex-exchanging sex for money, drugs, or other resources-were more common in homeless or marginally housed people than in those with stable housing. At six-to-nine-month follow-up, those who experienced an improvement in their housing status decreased their frequency of drug use, needle use, needle sharing, and unprotected sexual intercourse compared with people whose housing did not change.…”
Section: Stable Housingmentioning
confidence: 99%
“…19,20 From the wide spectrum of possible residential status, homelessness, the most severe form of precarious housing status, has received considerable attention, particularly in the literature on HIV risk behaviors. [21][22][23][24][25][26] Evidence seems to point towards homelessness as a factor that facilitates engagement in risk behaviors which, in turn, increases the likelihood of infectious disease transmission. 27 Beyond homelessness, the complexity of housing concept and its importance in health research have been recognized by several researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Housing instability has previously been associated with HIV risk behaviors, 40,41 while improved housing conditions have been associated with reductions in risky drug and sexual behaviors. 42 New York City is one of the most expensive cities in the United States to live.…”
Section: Discussionmentioning
confidence: 99%